Weight loss what works, what doesn't works and why diets don't work - Leutholtz, Brian C.; American College of Sports Medicine; Monterey Bay Video Production Co.; Insight Media (Indianapolis : Monterey Bay Video Production Co. [production] ; New York : Insight Media [distributor], 2006)
Reviews the shortcomings of dieting and presents a detailed discussion of how to lose weight successfully and safely. Also examines some of the more commonly held fitness-related myths and misconceptions
Title from title screen
Keywords: Weight loss; Diet; Reducing diets